Summary of Baseline Household Survey Results: Vinh Loi district Bac Lieu province Viet Nam - Truc, Ngo Thi Thanh; Ferrer, Alice J.; Tan Yen, Bui; Sebastian, Leocadio S. (2015)
The household baseline survey conducted in December 2014 to January 2015 collected data from 140 households in seven villages, including Tra Hat village, in Bac Lieu province, Vietnam. This is part of the baseline data collection activities in Tra Hat Climate Smart Village of the CGIAR Research Program on Climate Change, Agriculture and Food Security. The objective is to collect household baseline data where data in five or 10 years in the same households will be compared to capture changes that may occur over time. Results showed that the households were highly dependent on farming, particularly rice, for food and income. Farming, however, was characterized by low crop and commercialization index. They diversified income sources by engaging in off-farm work within the area or migrating to other places to find work. The market influenced more farmers’ decisions related to crops, but climate-related factors were becoming significant. Adaptation and mitigation measures need to be enhanced. Providing the farmers with correct information can help them make better decisions about the future. Access to land, increased production, few natural disasters in the area, and improved irrigation were likely the reasons for enough food supply among most of the households.